A novel soluble nano-catalysts in diesel–biodiesel fuel blends to improve diesel engines performance and reduce exhaust emissions. (1st January 2015) - Mirzajanzadeh, Mehrdad; Tabatabaei, Meisam; Ardjmand, Mehdi; Rashidi, Alimorad; Ghobadian, Barat; Barkhi, Mohammad; Pazouki, Mohammad
Graphical abstract: Highlights: Reporting a novel soluble (homogenous) amide-functionalized MWCNTs-CeO2 catalyst. Significant improvements in combustion of B20(90 ppm) compared to neat B20. NOx, CO, HC and soot were reduced by up to 18.9%, 38.8%, 71.4% and 26.3%, respectively. Increased power and torque by up to 7.81% and 4.91%, respectively. Decreased fuel consumption by 4.50%. Abstract: This study was aimed at synthesizing a novel soluble hybrid nanocatalyst to decrease emissions i.e., nitrogen oxide compounds (NOx ), carbon monoxide (CO), unburned hydrocarbons (HC) and soot, of a DI engine fueled with diesel–biodiesel blends. Moreover, enhancement of performance parameters i.e. power, torque and fuel consumption was also simultaneously targeted. The hybrid nanocatalyst containing cerium oxide on amide-functionalized multiwall carbon nanotubes (MWCNT) was investigated using two types of diesel–biodiesel blends (B5 and B20) at three concentrations (30, 60 and 90 ppm). The results obtained revealed that high surface area of the soluble nano-sized catalyst particles and their proper distribution along with catalytic oxidation reaction resulted in significant overall improvements in the combustion reaction specially in B20 containing 90 ppm of the catalyst B20(90 ppm) . More specifically, all pollutants i.e., NOx, CO, HC and soot were reduced by up to 18.9%, 38.8%, 71.4% and 26.3%, respectively, in B20(90 ppm) compared to neat B20. The innovated fuel blend also increased engine performance parameters i.e., power and torque by up to 7.81%, 4.91%, respectively, and decreased fuel consumption by 4.50%.